DAMPAK BANTUAN PEMBIAYAAN MODAL TERHADAP PENDAPATAN PELAKU USAHA MIKRO KECIL DAN MENENGAH DI KABUPATEN SUMBAWA - K Kamaruddin; Ika Fitriyani; I Nyoman Sutama (Pusat Riset dan Publikasi, 2023)
This study aims to determine the income of MSME actors before and after obtaining capital financing assistance from BMT Insan Samawa. The type of this research is comparative research. The data used is primary data obtained directly through interviews. The informants of this study were 80 MSME actors who were registered as BMT Insan Samawa customers. The data analysis technique is using the Two Means Difference Test, which includes paired samples statistics test, paired samples correlations test, and paired samples t-test. The results showed that there were differences in the income levels of MSME actors in Sumbawa Regency before and after receiving capital assistance from BMT Insan Samawa. The provision of capital assistance by BMT Insan Samawa has had a positive impact on the income of MSMEs in Sumbawa Regency. The average income earned by MSME actors after receiving capital assistance from BMT Insan Samawa has increased compared to the income earned before receiving capital assistance from BMT Insan Samawa.